Phase Contamination Characterization of Stepwise-built Functionally Graded Hydroxyapatite/Titanium (HA/Ti) Sintered under Various Atmospheres - Siti Nur Sakinah, Jamaludin; Shahnor, Basri; Faizal, Mustapha; Nuruzzaman, D. M.; Muhammad Ihsan, Abdul Latiff; Noor Mazni, Ismail (Trans Tech Publications Ltd, 2017)
Fourier Transform Infrared Spectroscopy (FTIR) and X-Ray Diffraction (XRD) test were utilized to detect the phase transformation of a HA/Ti Functionally Graded Material (FGM) prepared via Powder Metallurgy (PM) technique. The effects of oxygen (O2), nitrogen (N2), forming (N2+H2) and Argon (Ar) sintering atmospheres on the FGM specimens were examined by considering the gas flowing duration. It was found that the original metallurgical profile of pure Ti in HA/Ti FGM sintered under N2 atmosphere was almost preserved. However the carburization of the pure Ti was observed on the specimen. Medium alkyl halides (C-Br) and alkenes (-C=C-) stretches were detected, producing the dominant elements in the pure Ti layer of the specimen. The almost stable constituent element remains in the specimen sintered under flowing N2+H2 atmosphere as detected by XRD result. This proved the significance of controlling the sintering atmosphere during the entire sintering process. The results achieved reveal the high tendency of Ti and HA elements to react with the sintering environment, thus very precise furnace with controllable atmosphere is crucial for the fabrication of the HA/Ti FGM.